Scientific publications on women\'s health in Islamic Republic of Iran during three decades (1981 to 2012): A review - Narges Rostami Gooran; Azadeh Sayarifard; Maryam Nazari; Rahbari Maryam; Hamideh Javadinasab; Batoul Ahmadi (Payesh, 2018)
Objective: The present study aimed to identify the neglected aspects of womenchr('39')s health during the three decades after the Islamic Revolution of Iran. Methods: This was a descriptive review of the literature. All Persian and English articles published in journals from 20 March 1981.to 20 March 2013. The data were collected on  health status, determinants and health outcomes of Iranian women, regardless of age limit. Studies were reviewed for eligibility based on inclusion and exclusion criteria and duplicate studies were excluded. Then the information including year of publication, number of authors, 17 major diseases in women and infertility, SDH (social determinants of health), life stage and methods were recoded and were analyzed. Results: In all 1880 Persian articles and 4090 English articles were reviewed (a total of 5970 articles). The frequency of research type was 4.15% for reviews, 22.12% for interventional, 22.34% for comparative and 51.37% for descriptive studies. Most researches based on life cycle was about the reproductive age 76%, based on burden of disease was about pregnancy and its complications 30.12% and based on SDH factors was about education and awareness 6.36%. Conclusion: The findings suggest that although scientific publications on women’s health in Iran increased dramatically, no consistent trend observed nor the designs and topics showed integrative coherences.